2019
DOI: 10.1002/jcp.29107
|View full text |Cite
|
Sign up to set email alerts
|

CSE1L silence inhibits the growth and metastasis in gastric cancer by repressing GPNMB via positively regulating transcription factor MITF

Abstract: Human chromosomal segregation 1-like (CSE1L) gene functions as a key molecular mediator in cellular proliferation, invasion, and apoptosis. The association of CSE1L with tumor progression has been reported in diverse human cancers. A greater understanding of CSE1L molecular mechanism is beneficial for cancer treatment. In the current study, we show that CSE1L was highly expressed in gastric cancer (GC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…45 Li found that CSE1L acted as an oncogene in gastric cancer (GC), and knockdown of CSE1L suppressed GC cell proliferation and metastasis via inhibition of glycoprotein nonmetastatic melanoma protein B (GPNMB) expression. 46 In this study, analysis of GEO datasets (GSE110224 and GSE37364) and IHC analysis showed that CSE1L was upregulated in CRC. Spearman correlation analysis indicated that CSE1L was positively correlated with circ_0060745 and that CSE1L was inversely correlated with miR-4736.…”
Section: Discussionmentioning
confidence: 64%
“…45 Li found that CSE1L acted as an oncogene in gastric cancer (GC), and knockdown of CSE1L suppressed GC cell proliferation and metastasis via inhibition of glycoprotein nonmetastatic melanoma protein B (GPNMB) expression. 46 In this study, analysis of GEO datasets (GSE110224 and GSE37364) and IHC analysis showed that CSE1L was upregulated in CRC. Spearman correlation analysis indicated that CSE1L was positively correlated with circ_0060745 and that CSE1L was inversely correlated with miR-4736.…”
Section: Discussionmentioning
confidence: 64%
“…To date, although a number of predictive molecular markers (e.g., 1p/19q co-deletion and IDH1/2 mutations) have been identified as prognostic markers for glioma ( 33 35 ), more are urgently required, partly due to the great complexity of the molecular traits of glioma ( 36 ). GPNMB, a transmembrane glycoprotein, has been demonstrated to be involved in tumor progression ( 11 , 12 , 21 , 22 ), whereas its mechanistic effects on glioma progression and its prognostic role have not been thoroughly investigated. Therefore, the aim of the present study was to elucidate the prognostic role of GPNMB in glioma through data mining of publicly accessible datasets through validation by immunohistochemical staining of a tissue microarray.…”
Section: Discussionmentioning
confidence: 99%
“…GPNMB is not only expressed in normal tissues (e.g. skin, bone, urinary system and CNS tissues), but also abnormally expressed in pathological tissues such as glaucoma, colitis, liver injury and a variety of carcinoma tissues ( 9 ), such as breast ( 10 ), gastric ( 11 ) or pancreatic cancer ( 12 ). GPNMB is located on the cell membrane and intracellular organelles, such as melanosomes and lysosomes, and can also be secreted into the extracellular compartment ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human chromosomal segregation 1‐like ( CSE1L ) gene functions as an important mediator in cell nucleus, and is involved in cell proliferation, migration, and apoptosis. Overexpression of CSE1L has been shown to be associated with tumor development and cancerogenesis 70 . In a preclinical study on the lncRNA growth arrest‐specific transcript 5 gene ( GAS5 ), GAS5 ‐derived snoRNAs expression was upregulated to a DNA damage response p53 ‐dependently manner.…”
Section: The Lncrnas Mode Of Actionmentioning
confidence: 99%